2010
DOI: 10.1310/tsr1706-423
|View full text |Cite
|
Sign up to set email alerts
|

Oral Reading for Language in Aphasia (ORLA): Evaluating the Efficacy of Computer-Delivered Therapy in Chronic Nonfluent Aphasia

Abstract: Low-intensity ORLA, delivered by computer to individuals with chronic nonfluent aphasia, is efficacious and may be equivalent to ORLA delivered by an SLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 24 publications
(29 reference statements)
3
60
0
9
Order By: Relevance
“…The lexical treatment approaches have predominantly targeted reading text aloud (Cherney, 2010;Kim & Russo, 2010;Orjada & Beeson, 2005) or paired associated learning (Friedman, Sample, & Lott, 2002;Lott, Sample, Oliver, Lacey, Friedman, 2008). Taken as a whole, lexically focused treatments demonstrate improved reading for trained stimuli with limited generalization to untrained items and contexts.…”
mentioning
confidence: 99%
“…The lexical treatment approaches have predominantly targeted reading text aloud (Cherney, 2010;Kim & Russo, 2010;Orjada & Beeson, 2005) or paired associated learning (Friedman, Sample, & Lott, 2002;Lott, Sample, Oliver, Lacey, Friedman, 2008). Taken as a whole, lexically focused treatments demonstrate improved reading for trained stimuli with limited generalization to untrained items and contexts.…”
mentioning
confidence: 99%
“…Taggart, Turkle, and Kidd (2005), for example, observed interactions of elderly individuals with robots and found that they exhibited social reactions to the robots that reflected a sense of companionship. Evidence from aphasia comes from a study reported by Cherney (2010) on the efficacy of a treatment protocol, Oral Reading for Language in Aphasia (ORLA), which was administered to 25 individuals with nonfluent aphasia by an HC and, in a second condition, delivered by a computer program. No significant difference was observed in the outcomes of the two conditions.…”
Section: Conclusion: Results Provide Support For the Feasibility And mentioning
confidence: 99%
“…We selected Oral Reading for Language in Aphasia (ORLA; Cherney, 2004) for several reasons. This method is particularly well suited for telerehabilitation and has been used successfully with mild to moderate non-fluent aphasia (Cherney, 2010a; b). In addition, by design this oral reading treatment focuses on connected discourse and provides practice with speech rhythm and pacing, which we expected to be particularly beneficial to our participant given his frequent hesitations and blocking during oral language production (Cherney, 2010b).…”
Section: Methodsmentioning
confidence: 99%
“…This method is particularly well suited for telerehabilitation and has been used successfully with mild to moderate non-fluent aphasia (Cherney, 2010a; b). In addition, by design this oral reading treatment focuses on connected discourse and provides practice with speech rhythm and pacing, which we expected to be particularly beneficial to our participant given his frequent hesitations and blocking during oral language production (Cherney, 2010b). We modified the original protocol to suit the needs of our participant and employed the following six steps: reading single paragraphs aloud, locating words in the text, using words in sentences, reading multiple paragraphs independently, summarising paragraphs, and answering content questions.…”
Section: Methodsmentioning
confidence: 99%